Usefulness of zebrafish model to assess glomerular and tubular alterations induced by tenofovir - Gorgulho, Rita de Sousa (2015)
Tenofovir (TFV) is one of the most used antiretroviral drugs. However, it is associated with tubular damage with mitochondria as a possible target. Tubulopathy precedes glomerular dysfunction, thus classic markers of renal function like the glomerular filtration rate (GFR) do not detect early TFV damage. Prediction and management of drug induced renal injury (DIRI) rely on the mechanisms of the drug insult and in optimal animal models to explore it. Zebrafish (Danio rerio) offers unique advantages for assessing DIRI, since the pronephros is structurally very similar to its human counterpart and is fully developed at 3.5 days postfertilization. The main aim of the present work was to evaluate the effects of TFV, as well as its pro-drug, tenofovir disoproxil fumarate (TDF), on the GFR and in mitochondria morphology in tubular cells of zebrafish larvae. Lethality curves were performed to understand the relationship between drug concentration and lethality. LC10 was selected to explore the renal function using the FITC-inulin assay and to analyze the mitochondrial toxicity by electron microscopy on larvae exposed to TDF, TFV, paracetamol and gentamicin (positive controls) or water (negative control). Lethality curves showed that gentamicin was the most lethal drug, followed by TDF, TFV and paracetamol. Gentamicin and paracetamol decreased the GFR, but no differences were found for either TDF or TFV, when compared to controls (%FITC Control = 33±8; %FITC TDF = 35±10; %FITC TFV = 30±10; %FITC Gentamicin = 46±17; %FITC Paracetamol = 83±14). Tubular mitochondria from treated larvae were notably different from non-treated larvae, showing swelling, irregular shapes, decreased mitochondria network, cristae disruption and loss of matrix granules. These results are in agreement with the effects of these drugs in humans and thus, demonstrate that zebrafish larvae can be a good model to assess the functional and structural damage associated with DIRI.